2017
DOI: 10.21037/jss.2017.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Anterior lumbar interbody fusion (ALIF) as an option for recurrent disc herniations: a systematic review and meta-analysis

Abstract: Pooled evidence suggests that ALIF is a feasible approach for the treatment of recurrent disc herniations, demonstrating significant improvements in back and leg pain and minimal complications. These findings warrant further investigation in large prospective registries and multi-center studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…Several retrospective analyses and systematic reviews have reported a wide range of rates of retrograde ejaculation in patients who underwent anterior spine surgery. [30][31][32][33] There were no identifiable cases of retrograde ejaculation in our series, but we suspect that this is an underestimate of the true rate given the retrospective nature of this study. We did not identify any cases of intraoperative ureteral injury in patients undergoing transabdominal retroperitoneal ALIF, which is related to two important factors.…”
Section: Discussionmentioning
confidence: 68%
“…Several retrospective analyses and systematic reviews have reported a wide range of rates of retrograde ejaculation in patients who underwent anterior spine surgery. [30][31][32][33] There were no identifiable cases of retrograde ejaculation in our series, but we suspect that this is an underestimate of the true rate given the retrospective nature of this study. We did not identify any cases of intraoperative ureteral injury in patients undergoing transabdominal retroperitoneal ALIF, which is related to two important factors.…”
Section: Discussionmentioning
confidence: 68%
“…With miniTLIF, the operation time was 116–390 min, with TLIF — 102–365 min; blood loss — 51–578 and 225–961 ml, respectively; hospital stay — 2.3–10.6 and 2.9–14.6 days, respectively [ 40 ]. With ALIF, the average blood loss is 122 ml, the operation time is 89 min, and the hospital stay is 5.3 days [ 52 ]. Thus, in the studies analyzed, the surgical trauma with OLIF is less pronounced than that with TLIF and ALIF, as evidenced by comparative studies of these techniques [ 24 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…На сучасному етапі спінальної хірургії спондилодез є звичайним методом лікування дегенеративних захворювань поперекового відділу хребта, таких, наприклад, як грижі міжхребцевих дисків, спондилолістез, стеноз хребтового каналу [3][4][5][6][7][8]. Частіше спінальні хірурги виконують дискектомію без спондилодезу.…”
Section: вступunclassified